Translation and psychometric evaluation of the Persian version of the self-management behaviors questionnaire in patients with rheumatoid arthritis - Mehdi Rezaeian; Erfan Pourshahri; Poopak Mohaghegh; Azizallah Dehghan; Mostafa Bijani; Hamed Taherhaghighi (BMC Research Notes)
Abstract Objective Self-management behaviors play a critical role in controlling disease complications, improving treatment outcomes, and enhancing quality of life for Rheumatoid arthritis (RA) patients, a dedicated and comprehensive instrument with demonstrably strong validity and reliability is crucial for their assessment. To address this need, the present study undertook the translation and validation of the Persian version of the “Self-Management Behaviors Questionnaire” specifically for RA patients. Employing a cross-sectional research design, the study involved 334 participants from four Iranian cities. Following the meticulous translation of the original RA-SMBS instrument into Persian, a comprehensive evaluation of its psychometric properties was conducted using the established COSMIN criteria. Results The exploratory factor analysis (EFA) revealed statistically significant factor loadings ranging from 0.62 to 0.89 for all 23 items, indicating a robust underlying factor structure. Furthermore, the instrument demonstrated excellent internal consistency, with a Cronbach’s alpha coefficient of 0.92 for the entire scale. These findings collectively establish the Persian version of the Rheumatoid Arthritis Self-Management Behaviors Scale (RA-SMBS) as a reliable and valid tool. Consequently, healthcare administrators can confidently utilize this questionnaire to assess self-management behaviors in their RA patient population. This information can then be leveraged to develop and implement targeted programs and strategies aimed at enhancing self-management skills among individuals living with rheumatoid arthritis. Clinical trial number Not applicable.